Reverse Engineering as a Solution in Parts Restoration Process. (2017) - Sokół, Krzysztof; Cekus, Dawid
Abstract: The main purpose of this paper is to present and describe in details the method of transformation of real life object into a discrete one, on the basis of which the creation of surface – solid computer model will be shown. The investigated object is a motorcycle front fender in 1:12 scale. Due to incorrect assembly process the part has been damaged. The only method of solution is a restoration by means of digitalization and modeling with CAD software. The finished model is 3D printed and after completeness of this stage it will be used as a spare part.